Late Miocene hominin teeth from the Gona Paleoanthropological Research Project area, Afar, Ethiopia. - Simpson, Scott W; Kleinsasser, Lynnette; Quade, Jay; Levin, Naomi E; McIntosh, William C; Dunbar, Nelia; Semaw, Sileshi; Rogers, Michael J (Journal of Human Evolution, 2015)
Since 2000, significant collections of Latest Miocene hominin fossils have been recovered from Chad, Kenya, and Ethiopia. These fossils have provided a better understanding of earliest hominin biology and context. Here, we describe five hominin teeth from two periods (ca. 5.4 Million-years-ago and ca. 6.3 Ma) that were recovered from the Adu-Asa Formation in the Gona Paleoanthropological Research Project area in the Afar, Ethiopia that we assign to either Hominina, gen. et sp. indet. or Ardipithecus kadabba. These specimens are compared with extant African ape and other Latest Miocene and Early Pliocene hominin teeth. The derived morphology of the large, non-sectorial maxillary canine and mandibular third premolar links them with later hominins and they are phenetically distinguishable and thus phyletically distinct from extant apes. Copyright © 2014 Elsevier Ltd. All rights reserved.
Keywords: *Fossils/ah [Anatomy & Histology]; *Hominidae/ah [Anatomy & Histology]; *Tooth/ah [Anatomy & Histology]; Afar; Animals; Ardipithecus; Ardipithecus kadabba; Ardipithecus ramidus; Biological Evolution; Ethiopia; Fossils; Hominidae; Hominina; Late miocene; Miocene; Orrorin; Tooth; Western ethiopian escarpment; anatomy and histology; animal; anthropology; canid; dept.ant; evolution; fossil; hominid; morphology; peer-reviewed; tooth